Nail Fold Capillaroscopic Changes in Patients with Type 2 Diabetes Mellitus: An Observational, Comparative Study - Deepak Jakhar; Chander Grover; Archana Singal; Gopal Krushna Das; S. V. Madhu (Indian Journal of Medical Specialities)
Background: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disease affecting microvascular circulation causing complications such as retinopathy, nephropathy, and neuropathy. Nail fold capillaroscopy (NFC) is an in vivo study of microvascular circulation. Aim: The aim of this study is to describe and quantify NFC changes in type 2 diabetics. Materials and Methods: NFC was done for all 10 fingernails for 96 patients with T2DM (as per the American Diabetes Association criteria) and 40 healthy controls. The diabetics were further subdivided into two groups: those with microvascular complications (Group 1, n = 46) and those without any (Group 2, n = 50). Results: Demographic profile was comparable in both the groups. Overall, 80.2% (77/96) of the patients with T2DM showed NFC changes as compared to 12.5% of the healthy controls. Unique morphological alterations in T2DM were angulated and receding capillaries. Mean capillary density was overall reduced, especially in Group 1 (6.57 ± 1.02 capillary/mm) as compared to Group 2 (7.03 ± 1.09 capillary/mm) (P = 0.67). Overall, 89.13% of Group 1 patients had NFC changes as compared to 72% in Group 2 (P = 0.035). Specific morphological changes were also significantly more common in Group 1 than Group 2, including tortuosity (P = 0.035), meandering capillaries (P = 0.004), capillary dropouts (P = 0.012), and bizarre capillaries (P = 0.002). Limitations: A larger sample size study with different demographic populations could have provided a broader picture of NFC changes in T2DM. Conclusion: Our study suggests that NFC changes are correlated with microvascular complications in type 2 diabetics, possibly helping in noninvasive identification of patients at risk.